Pharmacokinetics and dosing rationale of Para-Aminosalicylic acid in children and the evaluation of the in vitro metabolism of Ethionamide, Terizidone and Para-aminosalicylic acid - Liwa, Anthony Cuthbert (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2012.